Results in liver transplantation using grafts from donors after controlled circulatory death: A single‐center experience comparing donor grafts harvested after controlled circulatory death to those harvested after brain death. Issue 1 (30th December 2019) - Otero, Alejandra; Vázquez, María Angeles; Suárez, Francisco; Pértega, Sonia; Rivas, Jose Ignacio; Mosteiro, Fernando; Gómez, Manuel
Abstract: Background: In recent years, interest in donation after cardiac death (DCD) has increased. Although DCD liver transplantation (LT) has demonstrated satisfactory long‐term outcomes, different studies have shown poorer patient and graft survival after DCD than after donation after brain death (DBD). This study aimed to evaluate the results of LT using controlled DCD (cDCD) donors, specifically the incidence of primary non‐function and ischemic cholangiopathy (IC), and to compare these results with those of LT using DBD in the same time period. Methods: Between June 2012 and July 2018, we performed 66 transplants using cDCD and 258 with DBD grafts. Results: The incidence of IC was similar in both groups (2% in DBD, 1.5% in DCD; P = .999). No significant differences were found for overall graft and patient survival rates between the groups at 1 and 2 years post‐transplantation. Conclusions: This study provided evidence that cDCD donors exhibit excellent graft and patient survival outcomes. When the warm ischemia time is <30 minutes and cold ischemia time is <6 hours, the graft and patient survival rates and the incidence of IC in DCD are similar to those in DBD, even when using donors without age restrictions.